H. H. Kung (1880-1967) and Multiple Religious Belonging: Christian-Confucian-Buddhist Interfaith Encounters in the Early Twentieth Century - Lin, Nan Kathy (Buddhist Christian studies, 2026)
H. H. Kung (1880-1967) is well known as a politician and financier who held prominent offices in Republican Era China (1911-1949). This paper argues that he is also an early example of what Peter Phan has called multiple religious belonging, well before theologians developed the category in a more open, post-Vatican-II era., First, this paper considers Kung's Christian influences. Kung encountered Oberlin missionaries in Shanxi Province at the end of the nineteenth century. He saw beloved Christian friends killed during the anti-foreign, anti-imperial, anti-Christian actions of the Boxer Rebellion. As an act of love for his friends, Kung journeyed to Oberlin to pursue further studies and to console the families of the departed. Kung brought his education to bear on his later years in leadership within the Republican government, as well as in his efforts with Ming Hsien, an Oberlin-affiliated Christian liberal arts school in Shanxi., Second, this paper considers Kung's legacy as a proud bloodline descendant of Confucius and an upholder of Confucian institutions. Kung's embrace of Confucian values can be seen in how conceptions of family inform his thinking and action, as well as in his support for the Temple of Confucius in Qufu in the late 1920s. I argue that Kung's Confucianism was a second aspect of his multiple religious identity., Third, this paper considers Kung's gifts of Buddhist material culture to Oberlin College. Kung promoted Asian culture abroad by cultivating ties to his alma mater. Kung gifted the College a Buddhist temple bell in 1929, and also supported the erection of a replica Buddhist temple in the 1940s. Tracking the legacies of the Buddhist bell and temple reveals a reception history of Buddhism in the United States, in a time of incipient religious pluralism. This paper suggests that Kung's quiet support of Buddhist material culture abroad should be read as a further prong of Kung's multiple religious belonging. [End Page 241] , The paper concludes by considering the importance of viewing other Republicanera thinkers in China through the lens of multiple religious belonging. This is significant as a matter of political theology and reminds us of the connected histories between Asia, North America, and elsewhere.